Abnormal cardiovascular sympathetic and parasympathetic responses to physical and emotional stimuli in depersonalization disorder - Owens, Andrew P.; David, Anthony S.; Low, David A.; Mathias, Christopher J.; Sierra-Siegert, Mauricio (Frontiers in Neuroscience, 2015)
Background Depersonalization disorder (DPD) is characterized by a subjective sense of unreality, disembodiment, emotional numbing and reduced psychogenic (sudomotor) sympathoexcitation. Aims Three related experiments utilized escalating physical and emotional challenges in 14 DPD participants and 16 controls aimed to elucidate (i) whether the cardiovascular sympathetic (SNS) and parasympathetic (PNS) nervous systems are implicated in DPD pathophysiology and (ii) if possible, to determine whether the blunted sympathoexcitation in DPD is peripherally or centrally mediated. Method Participants completed the Beck Anxiety Inventory (BAI), Dissociative Experience Scale (DES), and Cambridge Depersonalization Scale (CDS). Study I recorded heart rate (HR) and blood pressure (BP) during 5 min supine baseline, 3 min sustained handgrip (HG), 3 min cold pressor (CP) and 5 min 60° head-up tilt (HUT). In study II, HR, BP, and heart rate variability (HRV) were recorded during 5 min simultaneous 60° HUT and continuous presentation of unpleasant images (5 s per image). Study III examined HR and BP orienting responses (ORs) to simultaneous 60° HUT and pseudorandom presentation of unpleasant, neutral and pleasant images (5 s per image 3 min 25 s). OR data was grouped by image valence post hoc. Results DPD BAI (p = 0.0004), DES (p = 0.0002), and CDS (p ≤ 0.0001) scores were higher than controls. The DPD group produced diminished diastolic BP (DBP) (p = 0.045) increases to HG. Other indices were comparable between groups. DPD participants produced diminished systolic BP (SBP) (p = 0.003) and DBP (p = 0.002) increases, but greater (p = 0.004) HR increases to CP. In study II, DPD high frequency HRV (HF-HRV)—indicating parasympathetic vagal activity–was reduced (p = 0.029). In study III, DPD DBP was higher throughout the 5 s duration of HUT/pseudorandom unpleasant image presentation (1 s, p = 0.002, 2 s p = 0.033, 3 s p = 0.001, 4 s p = 0.009, 5 s p = 0.029). Conclusions Study I's BP pressor data supports previous findings of suppressed sympathoexcitation in DPD. The greater HR increases to CP, decreased HF-HRV in study II, and increased DBP during unpleasant ORs in study III implicates the SNS and PNS in DPD pathophysiology. These studies suggest the cardiovascular autonomic dysregulation in DPD is likely to be centrally-mediated.